Medical response to the Great East Japan Earthquake in Ishinomaki City - Tadashi Ishii (World Health Organization Regional Office for the Western Pacific, 2011)
Problem: The Ishinomaki Red Cross Hospital is the only designated disaster hospital in the Ishinomaki Medical Zone, Japan that was undamaged from the Great East Japan Earthquake in March 2011. The tsunami completely destroyed a large part of the Ishinomaki Medical Zone.Context: The Ishinomaki Red Cross Hospital was designed with the capability to respond to disasters. An instruction manual for responding to disasters had been developed and was exercised through drills. Action: In accordance with the manual, the hospital disaster task force was established. The Ishinomaki Zone Joint Relief Team coordinated medical support from organizations such as physicians associations, dental associations, self-defence forces medical teams, pharmacists associations, the Japanese Red Cross and relief teams from hospitals all over the country. In three days, the joint relief team directly visited all emergency shelters to make an initial assessment and to collect information about the number and state of health of evacuees, provision of food and drinking water and the availability of electricity, water and sewerage. Outcome: Initial assessment revealed that 35 emergency shelters lacked a sufficient food supply and that 100 shelters had unsanitary conditions. The joint relief team provided the Miyagi Prefecture government and the Ishinomaki municipal government with information about emergency shelters that did not have a sufficient food supply. As of 30 September, the activities of the joint relief teams were completed, and there was no outbreak of communicable diseases in the Ishinomaki Medical Zone. A total of 328 shelters with 46 480 evacuees were managed by the Ishinomaki Zone Joint Relief Team.Discussion: Advanced preparation to quickly establish an initial response system, expertise, and decision-making ability and the ability to get things done are required for disaster response management.